Environmental Sanitation and Household Rodent Presence Among Suspected Leptospirosis Cases: Findings from Makassar, Indonesia - Manyullei, Syamsuar; Sintikhe Mangedong,; Muh. Fajar Natsir,; Nasrah Nasrah, (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Leptospirosis is a zoonotic disease caused by the bacterium Leptospira interrogans. Residential areas frequently experience poor environmental sanitation, including waste accumulation, stagnant water, and rodent activity around households. Such conditions compromise environmental hygiene and facilitate the survival of Leptospira bacteria. Poor sanitation increases community exposure to environmental sources of infection, thereby elevating the risk of leptospirosis.  Exposure may occur through direct or indirect contact with contaminated water or soil, particularly when stagnant water is contaminated with rodent urine. This study aimed to assess household rodent presence among suspected leptospirosis cases and to examine its association with environmental sanitation conditions. Polymerase chain reaction (PCR) testing and GIS-based spatial mapping were incorporated to support diagnostic and spatial interpretation.Methods: This study employed a quantitative, descriptive cross-sectional observational design. The sample comprised 20 households of suspected leptospirosis patients selected through purposive sampling. Data were collected through direct household observation using a structured checklist.Results: Chi-square analysis indicated no statistically significant associations between sanitation indicators and signs of rodent presence, including stagnant water (p = 0.068), waste accumulation (p = 0.068), rodent entry pathways (p = 0.178), drainage condition (p = 0.305), and wastewater disposal systems (SPAL) (p = 0.136). All examined variables demonstrated p-values greater than 0.05, indicating no statistically significant associations with observable rodent indicators. Nevertheless, the SPAL variable showed a non-significant trend toward association (p = 0.136), although it did not reach the conventional 5% significance threshold.Conclusion: No statistically significant relationships were identified between household sanitation conditions including stagnant water, waste accumulation, drainage condition, wastewater disposal systems (SPAL), and clean water availability and signs of rodent presence. To mitigate rodent-related environmental health risks, communities are encouraged to improve environmental hygiene through proper waste management, routine maintenance of drainage systems, and the implementation of household-level rodent control measures.